Curative Effects of Oleanolic Acid on Formed Hypertrophic Scars in the Rabbit Ear Model. (27th December 2012) - Zhang, Hong; Zhang, Yan; Jiang, Yi-Ping; Zhang, Lan-Ke; Peng, Cheng; He, Kun; Rahman, Khalid; Qin, Lu-Ping
Abstract : Hypertrophic scarring is a common proliferative disorder of dermal fibroblasts characterized by collagen overproduction and excessive deposition of extracellular matrix (ECM). There is no consensus about the best therapeutics to produce complete and permanent improvement of scars with few side effects. To investigate the therapeutic effects of oleanolic acid (OA) on hypertrophic scars and explore the possible mechanism of action involved, a rabbit ear model with hypertrophic scars was established. OA (2.5%, 5%, and 10%) was given once daily to the scars for 28 consecutive days. As a result, OA significantly alleviated formed hypertrophic scars on rabbit ears. The levels of TGF-β 1, MMP-1, TIMP-1, and collagens I and III were notably decreased, and the number of apoptosis cells and mRNA expression of MMP-2, caspase-3, and caspase-9 were markedly increased in the scar tissue. The scar elevation index (SEI) was also evidently reduced. Histological findings exhibited significant amelioration of the collagen tissue. These results suggest that OA has the favorable curative effects on formed hypertrophic scars in the rabbit ear model, and the possible mechanism of action is that OA decreases HSFs proliferation and increases HSFs apoptosis by reduction of P311 gene expression and TGF-β 1 production, inhibition of TIMP-1 secretion, enhancement of MMP-2 activity, and subsequently facilitation of degradation of collagen types I and III.